Popular music in the Zion Christian Church - Rafapa, Lesibana (Muziki: Journal of Music Research in Africa, 2013)
The article dwells, in the main, in rationalizing the popularity of ZCC (Zion Christian Church) worship songs. Lest the point of this paper is misconstrued as a homogenization of the ZCC and the collective of South African black cultural groups, only segments of which belong to the ZCC, the reasons for qualifying this brand of music as popular are outlined. This discussion isolates features of the music that render it a refracted image of South African black folk music. The purpose is to trace the remoulding of such popular black music in the ZCC in order to pin down its identifiable functions. Aspects by which this kind of music belongs at least to sections of the black nation reflected overwhelmingly in the membership of the AIC (African Initiated Church) are also explored. Apart from probing the uniquely ZCC features of this kind of culturally inflected music, the peculiar way in which the music is put to use in this church is discussed, including how such uses differ from those evident in the greater community sharing its origins.
paid
Keywords: AFRICA; BLACK music; FOLK music; POPULAR music; RELIGION; RELIGIOUS Songs (Music); SOUTH African art; South African black folk music; ZCC; ZCC worship songs; ZION (Mormon Church); popular music